Under the radar - Westphal, James D.; Zhu, David H. (Strategic Management Journal, 2019)
[Research Summary: In this study, we reveal a previously unstudied type of board tie that may help firms manage competitive uncertainty. While firms face regulatory barriers to the use of board interlock ties as a strategy for reducing competition, we suggest that firms can circumvent these barriers by appointing the friends of competitors' chief executive officers (CEOs) to their boards. Our theoretical framework addresses the antecedents, maintenance, and performance consequences of such “board-friendship ties” to rivals. Our theory explains (a) why firms form and maintain board-friendship ties, where maintenance involves the reconstitution of broken ties and (b) how firms form and maintain these ties, by revealing the role of search firms in identifying the friends of rivals' CEOs. Empirical analyses of large-sample, longitudinal survey and archival data provide substantial support for our theory. Managerial Summary: Firms can and do reduce competition and increase performance by appointing the friends of competitors' CEOs to their boards, and search firms (headhunters) play a key role in forming and maintaining these “board-friendship” ties to competitors. While board interlock ties between close competitors are illegal and direct friendship ties between CEOs of competitors are relatively rare, board-friendship ties are common, and yet largely unknown to antitrust regulators and external stakeholders.]